PERANCANGAN RUMAH TINGGAL MENGGUNAKAN KONSEP HEMAT ENERGI - HUNAWA MOHI, SITI RABIA AR-RAHMA; Algiffar, M. Fauzhan; Pahrun, Apriyanto A. (Journal Of Building Architecture, 2023)
Indonesia, with a population of 275,773.8 million people, faces challenges in providing adequate housing. Electricity demand will reach 1,172 kWh per capita in 2022, dominated by fossil energy. The National Energy Council (DEN) seeks to increase the contribution of new renewable energy (EBT) to 25.9% by 2025. Sulawesi Island has various traditional houses, such as Tambii, Tongkonan, Walewangko, Mandar, and Dulohupa. Gorontalo City as the capital of Gorontalo Province has solar energy potential that has not been utilized optimally, especially in residential homes, due to the high price of solar panels. Gorontalo, with its hot climate, can utilize solar energy through solar panels to reduce dependence on conventional electricity. Awareness of energy sustainability and public education regarding renewable energy technology, especially solar panels, are very necessary to create efficient and environmentally friendly homes in line with the objectives of the National Energy Policy.